Analisis kemampuan komunikasi matematis siswa materi segiempat ditinjau dari self directing learning - Agnes Pujianti; Wahyu Setiawan; Heris Hendriana (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
The research was carried out with the aim of analyzing the mathematical communication skills of students on quadrilateral material in terms of self-directing learning. The method used is descriptive qualitative method. As many as 30 students of class VII A from SMP Pasundan 1 Cimahi were the subjects of this study. The data collection technique was in the form of a self-rating scale of self-directed learning (SRSSDL) questionnaire and a test instrument of 3 questions with indicators of written mathematical communication skills and interviews. The results showed that students with high self-directing learning had high mathematical communication skills by fulfilling all aspects of mathematical communication abilities. Students who are self-directing learning have average mathematical communication skills and are able to fulfill 2 aspects of mathematical communication skills, namely writing text and mathematical expression. Students whose self-directing learning is low have low mathematical communication skills which are only able to fulfill 1 aspect of mathematical communication ability, namely writing text and 1 indicator on the aspect of mathematical expression.